2022
DOI: 10.1039/d1fo03337a
|View full text |Cite
|
Sign up to set email alerts
|

Butyl-fructooligosaccharides modulate gut microbiota in healthy mice and ameliorate ulcerative colitis in a DSS-induced model

Abstract: Butyl-fructooligosaccharides (B-FOSs) are newly synthesized prebiotics composed of short-chain FOS (GF2, 1-kestose; GF3, nystose; GF4, fructofuranosyl-nystose; GF5, 1-F-(1-b-D-fructofuranosyl)-2-nystose) bound with one or two butyric groups by ester bonds. Previous in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Their results demonstrated that B-FOS significantly increased the mRNA expression of occludin in colonic tissue, decreased TNF-α, IFN-γ, and IL-8, and significantly increased cecal butyrate concentrations, which improved all the colitis pathological changes we summarize. 44…”
Section: The Application Of Different Kinds Of Functional Oligosaccha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their results demonstrated that B-FOS significantly increased the mRNA expression of occludin in colonic tissue, decreased TNF-α, IFN-γ, and IL-8, and significantly increased cecal butyrate concentrations, which improved all the colitis pathological changes we summarize. 44…”
Section: The Application Of Different Kinds Of Functional Oligosaccha...mentioning
confidence: 99%
“…Their results demonstrated that B-FOS significantly increased the mRNA expression of occludin in colonic tissue, decreased TNF-α, IFNγ, and IL-8, and significantly increased cecal butyrate concentrations, which improved all the colitis pathological changes we summarize. 44 As one of the most researched and widely used prebiotics, FOS have been recognized by the governments of countries and regions around the world, and are widely used in the fields of food, health care, medicine, cosmetics and animal feed. Similarly, like other prebiotics, FOS can also treat and improve UC by restoring the integrity of the intestinal barrier, improving intestinal dysbiosis, increasing the production of SCFAs, and activating a series of chain reactions such as immune response.…”
Section: Fructo Oligosaccharides (Fos)mentioning
confidence: 99%
“…An increase in the abundance of Bifidobacterium and the concentration of gut butyrate decreased the production of TNF-α, IFN-γ and IL-8, thus improving the symptoms of colitis. 79,80 FOSs also has a good therapeutic effect on obesity-related chronic inflammation. In the mouse model of nonalcoholic steatohepatitis induced by monosodium glutamate, FOSs significantly improved hepatic steatosis, inflammatory cell infiltration and hepatocyte swelling.…”
Section: Fructo-oligosaccharides (Foss)mentioning
confidence: 99%
“…8 Previous studies have preliminarily demonstrated that many prebiotics (e.g., fructo-oligosaccharides and galacto-oligosaccharides) can change, modify, and restore the gut microbiota ecosystem and also improve the function of intestinal barriers, which could contribute to UC adjuvant therapy. 9,10 Pectin is abundantly present in the primary cell wall and middle lamellae of plants. It has been proved that dietary fiber supplements of pectin can relieve intestinal inflammation and UC symptoms without toxic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…, fructo-oligosaccharides and galacto-oligosaccharides) can change, modify, and restore the gut microbiota ecosystem and also improve the function of intestinal barriers, which could contribute to UC adjuvant therapy. 9,10…”
Section: Introductionmentioning
confidence: 99%